Taxonomic review of the genus Erythrocricus Schubart, 1962 (Diplopoda, Spirobolida, Rhinocricidae) - Rodrigues, Patrícia Elesbão Silva; Rodrigues, Everton Nei Lopes (European Journal of Taxonomy, 2021)
We review the genus Erythrocricus Schubart, 1962 based on the type material of the species Erythrocricus sanguineostriatus (Schubart, 1962). We propose a new diagnosis, redescribe the type species, and propose a new synonymy and a new combination. In addition, a male-based key to both species recognized, including Erythrocricus electrofasciatus (Schubart, 1957), comb. nov. ex. Rhinocricus, is given.